A norma individual e concreta que documenta a incidência: a constituição do fato jurídico relacional e a homologação fazendária - Nardi, Ana Paula Gomes (2015)
This report discusses the formation of the tax credit through the act performed by the taxpayer, which are fully identified, based on the elements related to the tax payment: tax base, tax calculation due and subjects active and passive, following what prescribes the article nº 142 of the Law nº 5.172 / 66. The presence of the tax authorities in the tax credit formalized act implied the existence of administrative act that, after being informed of the tax legal fact authorizes the use of the electronic invoice. This change implied the possibility to express approval of the tax credit document promoted by the taxpayer. The electronic invoice use permit will be the focus of the work, analyzed under the approach of Constructivist epistemology